Impaired Cerebrovascular Hemodynamics are Associated with Cerebral White Matter Damage. Issue 2 (February 2014) - Purkayastha, Sushmita; Fadar, Otite; Mehregan, Aujan; Salat, David H; Moscufo, Nicola; Meier, Dominik S; Guttmann, Charles RG; Fisher, Naomi DL; Lipsitz, Lewis A; Sorond, Farzaneh A
White matter hyperintensities (WMH) in elderly individuals with vascular diseases are presumed to be due to ischemic small vessel diseases; however, their etiology is unknown. We examined the cross-sectional relationship between cerebrovascular hemodynamics and white matter structural integrity in elderly individuals with vascular risk factors. White matter hyperintensity volumes, fractional anisotropy (FA), and mean diffusivity (MD) were obtained from MRI in 48 subjects (75±7years). Pulsatility index (PI) and dynamic cerebral autoregulation (dCA) was assessed using transcranial Doppler ultrasound of the middle cerebral artery. Dynamic cerebral autoregulation was calculated from transfer function analysis (phase and gain) of spontaneous blood pressure and flow velocity oscillations in the low (LF, 0.03 to 0.15 Hz) and high (HF, 0.16 to 0.5 Hz) frequency ranges. Higher PI was associated with greater WMH ( P <0.005). Higher phase across all frequency ranges was associated with greater FA and lower MD ( P <0.005). Lower gain was associated with higher FA in the LF range ( P =0.001). These relationships between phase and FA were significant in the territories limited to the middle cerebral artery as well as across the entire brain. Our results show a strong relationship between impaired cerebrovascular hemodynamics (PI and dCA) and loss of cerebral white matter structural integrity (WMH and DTI metrics) in elderly individuals.